Information Practices of Baby Boomers as Caregivers - Seow, Khuan; Caidi, Nadia (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Canada has an aging population with the fastest growing age groups (80 and 45-64 years old) vulnerable to age-related diseases such as Alzheimer’s disease. Caregiving responsibilities often fall to the family members of the afflicted without much attention and consideration being placed on the information needs of these caregivers. We call for a better understanding of these caregivers' information needs and uses by social policy makers as well as information providers. La population du Canada a tendance à vieillir considérablement, avec la hausse la plus rapide dans les groupes d’âge (80 et 45 à 64 ans). Les personnes âges sont très vulnérables à toute sorte de maladies, telles que la maladie d’Alzheimer. La responsabilité revient souvent aux membres de la famille qui doivent prendre soin des personnes atteintes de cette maladie. Or, nous ne connaissons que peu de chose sur les besoins en information des personnes qui prennent soin de ces malades de l’Alzheimer : qui sont-ils ? Quelles sont leurs sources...